IMPROVEMENT OF E-GOVERNANCE MECHANISMS IN UKRAINE IN THE CONDITIONS OF DIGITAL TRANSFORMATIONS - Antonova, Liudmyla; Mokhova, Julia (Public Administration and Regional Development, 2022)
The article substantiates that the development of e-government is the main prerequisite for building an efficient digital market in Ukraine, the digital economy, further integration of the country into the EU digital single market. The aim of the work is to identify areas for improving e-government mechanisms in Ukraine to create an efficient digital market, develop the digital economy and increase the country's competitiveness. The main problems of e-government development, digital development of the country are highlighted: ecosystem (weak state policy on incentives and incentives for innovation economy, underdeveloped investment capital market, outdated education system, shortage of highly qualified personnel), institutional (low involvement of government agencies in implementing the Digital Economy Concept). and society, inconsistency of relevant legislation with global challenges and opportunities), infrastructure (low level of digital infrastructure coverage, unequal access of citizens to digital technologies and new opportunities), e-government and governance (low level of automation and digitalization of public services due to low motivation government agencies). It is proved that the development of e-government plays a key role in ensuring economic and social progress in the country. There are identified the directions of improvement of e-government mechanisms in Ukraine in the field of telecommunication networks (development of broadband subscriber access, system of telecommunication networks that meets European standards, development, modernization and optimization of telecommunication infrastructure elements), e-commerce infrastructure and online interaction of business entities e-IDAS regulations, electronic interaction system, e-commerce, development roadmap), digital skills, electronic document management (modernization of infrastructure equipment; digital educational resources, common criteria for assessing the quality of electronic documents, delimitation of access to information by various means of protection), e- medicine (single medical information space, national roadmap, implementation of e-projects). The implementation of these areas of development of e-government mechanisms will create an effective system of public administration with the use of digital technologies.